GAS TURBINE JET ENGINE - Lokotko, A. V. (European Journal of Applied Sciences, 2021)
The concept of a gas turbine jet engine is proposed. The purpose of the development is to increase the thermal efficiency of the engine by increasing the temperature of the working fluid. The engine is a Segner wheel type device with a rotating combustion chamber and tangentially mounted nozzles. The torque is generated by the reaction force of the jets emanating from the nozzles. Full expansion of the working fluid takes place in a system of rotors installed coaxially with the combustion chamber and also equipped with jet nozzles. Cooling of the combustion chamber and chamber nozzles is carried out by a liquid metal coolant circulating due to centrifugal forces in combination with the thermosiphon effect. Calculated estimates show that at a working fluid temperature corresponding to the combustion temperature of a stoichiometric mixture of hydrocarbon fuel with air, the thermal efficiency in the design mode is 0.47, the specific fuel consumption is 0.25 kg / kWh, which is comparable with the corresponding indicators for diesel engines ... The device received: a patent of the Russian Federation for an invention and a German patent for a utility model.